Dynamic in vitro hemocompatibility of oligoproline self-assembled monolayer surfaces. (29th July 2022) - Mzyk, Aldona; Imbir, Gabriela; Noguchi, Yuri; Sanak, Marek; Major, Roman; Wiecek, Justyna; Kurtyka, Przemyslaw; Plutecka, Hanna; Trembecka-Wójciga, Klaudia; Iwasaki, Yasuhiko; Ueda, Masato; Kakinoki, Sachiro
Abstract : The blood compatibility of self-assembled monolayers (SAMs) of oligoproline, a nonionic antifouling peptide, was investigated using the cone-and-plate assay imitating arterial blood flow conditions. Abstract : The blood compatibility of self-assembled monolayers (SAMs) of oligoproline, a nonionic antifouling peptide, was investigated using the cone-and-plate assay imitating arterial blood flow conditions. End-capped oligoprolines composed of 6 and 9 proline residues (Pro6 and Pro9) and a Cys residue were synthesized for preparing SAMs (Pro-SAMs) on Au-sputtered glass. The surface of Pro-SAMs indicated hydrophilic property with a smooth topology. The adsorption of blood components and the adhesion of blood cells, including leukocytes and platelets, were strongly suppressed on Pro-SAMs. Moreover, Pro9-SAM did not trigger the activation of platelets ( i.e., the conformational change of GPIIb/IIIa and P-selectin (CD62P) expression on platelets and the formation of aggregates). Our results demonstrate that Pro9-SAM completely inhibited acute thrombogenic responses and the activation of platelets under dynamic conditions.